Odpowiedzi

2009-10-14T19:20:44+02:00
1)¾ + ⅔ ÷ (-8/12) =-2/3
2)(2 - 1/7) × 3 / 2 + 0,6 =2 61/70
3)(⅓ + 2/7 ) : (1 - 1/9) + 3/7 =1 15/49
2009-10-14T19:23:55+02:00
1. ¾ + ⅔ ÷ (-8/12) = ¾+⅔*(-12/8) = ¾+1 = 1¾

2. (2 - 1/7) × 3 / 2 + 0,6 = 1 6/7*3/2,6=13/7*3 / 2,6 = 39/7*10/26 = 390/182 = 2 26/182 = 2 13/91

3. (⅓ + 2/7 ) : (1 - 1/9) + 3/7 = (7/21+6/21):8/9+3/7 = 13/21*9/8+3/7 = 39/56+3/7 = 39/56 + 24/56 = 63/56= 1 7/56 = 1⅛
2009-10-14T20:01:59+02:00
1)=3/4+2/3*(-12/8)=3/4-4/4=-1/4
2)=(14/7-1/7)*3/2+6/10=13/7*3/2+6/10=39/14+6/10=390/140+84/140=474/140=3 54/140
3)=(7/21+6/21)÷(9/9-1/9)+3/7=13/21÷8/9+3/7=13/21*9/8+3/7=117/168+3/7=117/168+72/168=189/168=1 21/168